Purchase Decisions: The Role of Content and Augmented Reality Mediated by Purchase Interest - Windarko, Windarko (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of Content Marketing and Augmented Reality (AR) on Purchase Decision of beauty products on marketplace applications , with Purchase Intention as a mediator variable . The emergence of digital marketing technology such as Virtual Try-On features on platforms like Shopee and TikTok Shop has been reshaped consumer behavior in making purchase decisions . This research employs a quantitative method using Structural Equation Modeling (SEM) based on Partial Least Squares , analyzed through SmartPLS 4.0. The results show that Augmented Reality has a significant and positive effect on Purchase Intention and indirectly influences Purchase Decision through Purchase Intention . On the others hand , Content Marketing does not mean affect Purchase Intention , but it directly affects Purchase Decision . These findings suggest that immersive experiences enabled by AR are more effective in stimulating consumers ' intention to buy than conventional marketing content.